Assessment of Water Balance Components of Bhadar River Basin Using SWAT Model - Kelaiya, Jainish; Rank, P. H. (International Journal of Bio-resource and Stress Management, 2019)
Knowledge of water balance and water yield of a river basin is an indispensable prerequisite in the sustainable management of water resources at basin level. Components of water balance are influenced by climate & physical characteristics of the catchment such as morphology, land use and soil. Therefore, understanding the relationship between these physical parameters and hydrological components is necessary to access the hydrologic response to climate and land cover variability in determining the water availability. The SWAT model is the tool to assess the water balance components of the hydrological cycle like rainfall, runoff, evapotranspiration and groundwater recharge under given land use, management and climate. The runoff and groundwater recharge assessment are very useful for the water resources development and planning. This study was undertaken for the Bhadar River basin divided into 16 watersheds and total drainage area of 7330.40 km2with the help of remote sensing and GIS techniques. The climatic, discharge and sediment yield data were divided into calibration period (1981-2000) and validation period (2001-2010). The climatic and discharge data, sediment data, SRTM-DEM imagery, soil maps and land use/cover classification from LISS IV imagery are used as primary inputs for SWAT model. SWAT model provides a better description of water balance of the watershed. The average annual rainfall, runoff, evapotranspiration, percolation to shallow aquifer and recharge to deep aquifer in the basin is 670, 243.67, 252.9, 150.14, and 7.51 mm, respectively. The annual average runoff is 36.37% of the average annual rainfall.